Concepciones y Comportamientos de Cuidadores Frente a las Manifestaciones Afectivo-Sexuales de Adolescentes con Discapacidad Intelectual (2019)
This research project aims to analyze the conceptions and behaviors of caregivers through the media, as well as the manifestations of adolescent sexuality in the condition of mild and moderate intellectual disability. This study took place in the city of Bogotá after the participation of 4 (four) professional caregivers from the areas of health and social sciences, who explain in depth the interview to the expression of the personal, behavioral and environmental factors that arise in the moment in which the sexual manifestation of those who care for and respond in this way to the beliefs, socio cultural influence, behaviors, and social norms that are related. In the results, it was possible to show the ignorance and the refusal to assume sexuality first, as an aspect inherent to the human being in the not only biologizes and second, as an act of co-responsibility.